Evaluation of Implementing Combined Lecture, Demonstration, and Question-Answer Methods in the Fiqh Lesson - Yuniendel, Ratna Kasni; Trinova, Zulvia (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
The purpose of this research was to find out how the planning, implementation, and evaluation of the combination of lecture, demonstration, and question and answer methods in Fiqh lessons on obligatory prayers material class VII (seventh grade) at State Islamic Junior High School of 1 Padang. The research type was qualitative field research. The instruments of this research were interviews and observation. There were two respondents in this research. They are Primary and secondary respondents. The primary respondents were 2 Fiqh teachers and ten students. Meanwhile, the principal and deputy curriculum as secondary respondents in strengthening the results of this research. The results of this research are (1) the teacher of Fiqh's lesson was well organized in the planning of the lecture, demonstration, and question and answer methods, (2) the implementation of the lecture, demonstration, and question and answer methods is not fully by the lesson plan, especially in applying technology as a learning media in Fiqh lessons. Therefore, it was focused on the teacher's explanation in front of the class. (3) Teachers carried out their roles well as facilitators for students who had not understood the learning material and provided a material review to strengthen students' understanding of learning. However, the evaluation did not measure the achievement of students' learning objectives.